2013
DOI: 10.2298/jas1301041f
|View full text |Cite
|
Sign up to set email alerts
|

The effect of salinity on germination, emergence, seed yield and biomass of black cumin

Abstract: Salinity sensitivity of black cumin (Nigella sativa L.) was studied to determine salinity effects on germination, emergence, biological yield, seed yield and plant height. A set of experiments were conducted under completely randomized design in the germinator, greenhouse and field. Seeds of black cumin were grown in a growth chamber irrigated with normal water, electric conductivity (EC) of 0.3 dS m-1 as the control, and treatments amended with NaCl to obtain EC from 3 to 39 dS m-1. Different EC treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The mean germination time increased with the reduction of water potential, especially at the lower temperature of 15 °C (Table 1). Similar effects were observed in seed germination, seedling emergence and seedling survival of Nigella sativa in the laboratory and the field (Faravani et al, 2013). Moreover, our results were in agreement with the findings of Javadi et al (2014) and Ahmadian et al (2015) who found that high levels of salinity can significantly inhibit seed germination in black cumin.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The mean germination time increased with the reduction of water potential, especially at the lower temperature of 15 °C (Table 1). Similar effects were observed in seed germination, seedling emergence and seedling survival of Nigella sativa in the laboratory and the field (Faravani et al, 2013). Moreover, our results were in agreement with the findings of Javadi et al (2014) and Ahmadian et al (2015) who found that high levels of salinity can significantly inhibit seed germination in black cumin.…”
Section: Resultssupporting
confidence: 93%
“…In particular, increasing of salinity until 16 dS m -1 reduced the seed germination percentage of Nigella sativa and no germination occurred in the highest salinity stress of 20 dS m -1 (Javadi et al, 2014). Germination percentage drastically declined and was delayed with increase of osmotic stress due to NaCl in MPa lower than -0.9 (Ahmadian et al, 2015) and in salinity stress below 21 dS m -1 (Faravani et al, 2013). Conversely, as reported by Hajar et al (1996) the seeds showed a germination rate of 95% to 82% in less than a week in salinity 150 ml mol at a constant temperature of 25 °C, and suggest that black cumin is a salt tolerant plant.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Germination speed depended both on the concentration of NaCl in the medium, and on the variety. Negative effect of NaCl on the germination speed was determined by Faravani et al (2013) in his studies. Draught (Shahverdikadi et al, 2011) and temperature (Gairola et al, 2011) also exert great inffluence on the speed of germination.…”
Section: Resultsmentioning
confidence: 99%